Postcolonoscopy Appendicitis: A Delayed Complication - Al Hillan, Alsadiq (Cureus, 2020)
Colonoscopy is a procedure that enables a physician (usually a gastroenterologist) to directly image and examine the entire colon. It has both diagnostic and therapeutic benefits with a relatively low morbidity rate. Complications have been well described in the literature. Nevertheless, it is necessary for operators to be aware of the rare complications of colonoscopy. Acute appendicitis is an unusually rare occurrence following a colonoscopy, and it can be easily confused with other complications of the procedure. Prompt recognition of this complication can lead to early, effective treatment, and delayed diagnosis can lead to serious results. We present a case of a 33-year-old man who underwent a routine colonoscopy with no intraoperative complication who presented with appendicitis two weeks later as a rare delayed side effect; such a delayed presentation has not been described in the literature previously. This case highlights that appendicitis should be considered in the differential diagnosis of right-sided lower abdominal pain following a colonoscopy.